Komunikasi Tokoh Politik dan Kesadaran Berpolitik Generasi Z - Tanuja, Vico; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research explores the political awareness of the youth in DKI Jakarta, focusing on the impact of exposure to corruption news on their political perceptions. The younger generation tends to rely on social media platforms, such as Instagram and TikTok, as their primary sources of political information. Regular exposure to corruption news leads to negative perceptions of politics and a decline in trust in government institutions. Politicians perceived rigid and sensitive political communication also contributes to the youth's apathy towards politics. Despite being seen as a breath of fresh air, concerns exist regarding the lack of experience and adequate representation among the younger generation. Political participation varies, with some participants engaging only formally. There is also a debate regarding priorities between political awareness and political participation. In conclusion, the political awareness of the youth is susceptible to being low due to exposure to corruption news, impacting their political participation. Improved political communication and adequate representation are necessary to encourage active involvement of the younger generation in politics. Penelitian ini mengeksplorasi kesadaran berpolitik generasi muda di DKI Jakarta, di tengah paparan berita korupsi, khususnya terkait persepsi politik mereka. Generasi muda cenderung mengandalkan media sosial, seperti Instagram dan TikTok, sebagai sumber utama informasi politik. Paparan berita korupsi secara rutin menyebabkan persepsi negatif terhadap politik dan penurunan kepercayaan pada lembaga pemerintahan. Penelitian ini menggunakan Teori Komunikasi Massa, Teori Kultivasi dan Teori Komunikasi Politik, dengan menggunakan pendekatan kualitatif dan wawancara mendalam sebagai teknik pengumpulan data. Didapatkan hasil bahwa komunikasi politik yang dianggap kaku dan sensitif oleh tokoh politik juga berkontribusi pada apatis generasi muda terhadap politik. Meskipun generasi muda dianggap membawa angin segar, ada kekhawatiran terkait pengalaman dan representasi yang kurang. Partisipasi politik bervariasi, dengan beberapa informan hanya berpartisipasi secara formalitas. Terdapat juga perdebatan seputar prioritas antara kesadaran berpolitik dan partisipasi politik. Kesimpulannya, kesadaran berpolitik generasi muda rentan rendah akibat paparan berita korupsi, memengaruhi partisipasi politik mereka. Komunikasi politik yang lebih baik dan representasi yang memadai diperlukan untuk mendorong keterlibatan aktif generasi muda dalam dunia politik.